Similar Arbuscular Mycorrhizal Fungal Communities in 31 Durum Wheat Cultivars (Triticum turgidum L. var. durum) Under Field Conditions in Eastern Canada - Stefani, Franck; Dupont, Sarah; Laterrière, Mario; Knox, Ron; Ruan, Yuefeng; Hamel, Chantal; Hijri, Mohamed (Frontiers in Plant Science, 2020)
Wheat is among the important crops harnessed by humans whose breeding efforts resulted in a diversity of genotypes with contrasting traits. The goal of this study was to determine whether different old and new cultivars of durum wheat (Triticum turgidum L. var. durum) recruit specific arbuscular mycorrhizal (AM) fungal communities from indigenous AM fungal populations of soil under field conditions. A historical set of five landraces and 26 durum wheat cultivars were field cultivated in a humid climate in Eastern Canada, under phosphorus limiting conditions. To characterize the community of AMF inhabiting bulk soil, rhizosphere and roots, MiSeq amplicon sequencing targeting the 18S rRNA gene (SSU) was performed on total DNAs using a nested PCR approach. Mycorrhizal colonization was estimated using root staining and microscope observations. A total of 317 amplicon sequence variants (ASVs) were identified as belonging to Glomeromycota. The core AM fungal community (i.e. ASVs present in > 50% of the samples) in the soil, rhizosphere and root included 29, 30 and 29 ASVs, respectively. ASVs from the genera Funneliformis, Claroideoglomus and Rhizophagus represented 37%, 18.6% and 14.7% of the sequences recovered in the rarefied dataset, respectively. The two most abundant ASVs had sequence homology with the 18S sequences from well-identified herbarium cultures of Funneliformis mosseae BEG12 and Rhizophagus irregularis DAOM 197198, while the third most abundant ASV was assigned to the genus Paraglomus. Cultivars showed no significant difference of the percentage of root colonization ranging from 57.8% in Arnautka to 84.0% in AC Navigator. Cultivars were generally associated with similar soil, rhizosphere and root communities, but the abundance of F. mosseae, R. irregularis and Claroideoglomus sp. sequences varied in Eurostar, Golden Ball and Wakooma. Although, these results were obtained in one field trial using a non-restricted pool of durum wheat and at the time of sampling, that may have filtered the community in biotopes. The low genetic variation between durum wheat cultivars for the diversity of AM symbiosis at the species level suggests breeding resources need not be committed to leveraging plant selective influence through the use of traditional methods for genotype development.